2018
DOI: 10.1007/s00262-018-2196-y
|View full text |Cite
|
Sign up to set email alerts
|

Levels of peripheral blood polymorphonuclear myeloid-derived suppressor cells and selected cytokines are potentially prognostic of disease progression for patients with non-small cell lung cancer

Abstract: Polymorphonuclear-MDSC (PMN-MDSC) have emerged as an independent prognostic factor for survival in NSCLC. Similarly, cytokine profiles have been used to identify subgroups of NSCLC patients with different clinical outcomes. This prospective study investigated whether the percentage of circulating PMN-MDSC, in conjunction with the levels of plasma cytokines, was more informative of disease progression than the analysis of either factor alone. We analyzed the phenotypic and functional profile of peripheral blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 66 publications
0
32
0
Order By: Relevance
“…[101][102][103] Neutrophils and circulating neutrophil microRNAs serve as biomarkers for detection of NLSLC and are an independent negative predictor of survival in patients with advanced disease. [104][105][106] Mechanistic studies on the role of neutrophils in MPE are warranted given their immunosuppressive role in NSCLC and adverse prognostic value in MPE. 107 Dendritic cells (DCs) are professional antigen presenting cells (APCs) that cross-present antigens, induce adaptive immune responses, and regulate the immune system by modulating T and B lymphocyte antigen specific responses via their major histocompatibility (MHC) class I and II receptors and ability to produce IL-12 family cytokines.…”
Section: Innate Immunity Within the Mpementioning
confidence: 99%
“…[101][102][103] Neutrophils and circulating neutrophil microRNAs serve as biomarkers for detection of NLSLC and are an independent negative predictor of survival in patients with advanced disease. [104][105][106] Mechanistic studies on the role of neutrophils in MPE are warranted given their immunosuppressive role in NSCLC and adverse prognostic value in MPE. 107 Dendritic cells (DCs) are professional antigen presenting cells (APCs) that cross-present antigens, induce adaptive immune responses, and regulate the immune system by modulating T and B lymphocyte antigen specific responses via their major histocompatibility (MHC) class I and II receptors and ability to produce IL-12 family cytokines.…”
Section: Innate Immunity Within the Mpementioning
confidence: 99%
“…Furthermore, MDSCs can contribute to patient resistance to immunotherapy (22,23). Several studies have examined the association between the MAGE-A4 and NY-ESO-1 expression levels and survival (18,(24)(25)(26)(27)(28)(29), as well as the association between the MDSCs infiltrated in the tumor microenvironment and the survival of patients with different types of lung cancer (30)(31)(32)(33). However, the prognosis of the association between the MAGE-A4 or NY-ESO-1 and MDSCs has yet to be confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Early evidence supported that MDSCs level was associated with clinical stage and distant metastasis in many human cancers including HNSCC, and surgical excision of tumors could decrease the concentration of peripheral blood MDSCs [27][28][29][30]29]. Hence, we addressed the number of infiltrated MDSCs by IHC in OSCC tissues and found that MDSCs were increased significantly in tumor stroma that was near to OSCC cells.…”
Section: Discussionmentioning
confidence: 91%